Merefleksi Konsep Tuhan Menurut Ulangan 6:4 dan Implikasinya dalam Pemahaman Trinitas - Candra Gunawan Marisi; Alex Djuang Papay; Upa Silaen; Jabes Pasaribu (Sekolah Tinggi Teologi Real Batam, 2024)
The views of certain groups within Christianity include the arguments of Arius (Jehovah's Witnesses), who asserts that although Jesus possesses a special nature, He remains human and therefore should not be regarded as more than merely a